Dispensasi Perkawinan Anak dibawah Umur menurut UU Perkawinan dengan Al Maqasyid Syariah - Rizqi Tri Lestari; Jejen Hendar (Jurnal Riset Ilmu Hukum, 2022)
Abstract. To establish a marriage, there are several terms and conditions that have been regulated in Law No. 16 of 2019 on amendments to Law No. 1 of 1974 on marriage, one of which relates to age restrictions. In fact, many have entered into marriages below the minimum age limit prescribed by the law on marriage. The purpose of the authors of this study is to determine the dispensation of underage marriage according to the Marriage Law and its implementation in the case of Decision number 250/Pdt.P/2021/PA.SOR, as well as knowing the consideration of judges in the determination of the dispensation of marriage underage in religious courts is associated with Almaqasyid Sharia. The method of approach conducted in this study is normative juridical approach. Data collection techniques conducted by the author is the study of literature. The research specification used is descriptive analysis. The results of the author's research, the consideration of judges in determining the dispensation of marriage underage in religious courts in point Darurriyah one of them to maintain offspring, and avoid poverty. This is in line with the purpose of marriage in Islamic law in Article 53 of the compilation of Islamic law which explains that resisting harm takes precedence over taking good. Abstrak. Untuk melangsungkan Perkawinan, terdapat beberapa syarat dan ketentuan yang telah diatur dalam Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan, salah satunya berkaitan dengan batasan umur. Tujuan penulis melakukan penelitian ini yaitu untuk mengetahui dispensasi perkawinan dibawah umur menurut Undang-Undang Perkawinan dan Implementasinya dalam Kasus Putusan Nomor 250/Pdt.P/2021/PA.SOR, serta mengetahui pertimbangan hakim dalam penetapan dispensasi perkawinan dibawah umur di Pengadilan Agama dikaitkan dengan Almaqasyid Syariah. Metode pendekatan yang dilakukan dalam penelitian ini yaitu pendekatan Yuridis Normatif. Teknik pengumpulan data yang dilakukan oleh penulis adalah dengan studi kepustakaan. Spesifikasi penelitian yang digunakan adalah Deskriptif Analisis. Hasil Penelitian penulis, Pertimbangan Hakim dalam Penetapan Dispensasi Perkawinan dibawah Umur di Pengadilan Agama dalam Point Darurriyah salah satunya untuk memelihara keturunan, dan menghindari kemadharatan. Hal ini selaras dengan tujuan perkawinan dalam hukum islam dalam Pasal 53 Kompilasi Hukum Islam yang menjelaskan bahwa menolak kerusakan lebih didahulukan dari pada mengambil kebaikan.